Develop and test a micro-pump based on acoustic impedance miss match - Ng, Koon Chye. (2012)
This project involved in the design, fabrication and testing of a valveless pump model. A simple micro-pump was developed based on acoustic impedance mechanism. Previous open loop model on measurement of pressure head and mean flow rate were examined. Nevertheless, this report was tracing on the development process of a closed loop system from its design stages to fabrication, and finally testing. The closed loop system was examining on the direction and velocity of the flow.